Ankylosing enthesitis, dactylitis, and onychoperiostitis in male DBA/1 mice: a model of psoriatic arthritis - Lories, R (2004)
Materials and methods: Aging male DBA/1 mice from different litters were caged together (4–6 mice per cage) at the age of 12 weeks, checked twice a week for signs of arthritis, and killed at different times. Hind paws were dissected and processed for histology. Results: Disease incidence varied between 50% and 100% in four different experiments. Besides clinical signs of arthritis, nail abnormalities were noticed. Pathological examination showed the occurrence of dactylitis characterised by diffuse neutrophil infiltration in 6 of 50 paws examined. Onycho-periostitis with progressive destruction of the nail bed and the underlying distal phalanx was seen in 5 of 50 paws examined. Conclusions: Although dactylitis and onychoperiostitis are rare manifestations of the disease process, these data strongly suggest that spontaneous arthritis in aging male DBA/1 mice shares important features with human psoriatic arthritis. This model may therefore be an important tool to study links between stress, sex, inflammation, and new bone formation with particular relevance to human psoriatic arthritis.